Approximating Generalised Cornu Spiral With Low Energy Curve - Chan , Chiu Ling (2012)
The computations of visual pleasing and mathematically fair curve are an ongoing process. In the earlier literature, researchers have been studying the smooth curve, or in a more technically term, the fair curve through the physical approach known as elastica, Elastica means a thin strip of elastic material. Daniel Bernoulli stated the elastica as variational problem in terms of strain energy and Malcom (1977) mentioned that the simplest way to characterize a spline mathematically is with the fact that a spline assumes a shape which minimizes its elastic strain energy.